Determinants and Outcome of Metabolic Acidosis in Diarrheal Children Under 5 Years of Age in an Urban Critical Care Ward in Bangladesh - Sharifuzzaman MBBS; Monira Sarmin MBBS, MCPS; Tahmeed Ahmed MBBS, PhD; Tahmina Alam MBBS; Shoeb Bin Islam MBBS; Md. Munirul Islam MBBS, PhD; Mohammod Jobayer Chisti MBBS, MMed, PhD (SAGE Publishing, 2017)
We evaluated the independent determinants and outcome of metabolic acidosis in diarrheal children. Children under 5 years of age admitted with diarrhea and severe respiratory distress in the critical care ward at Dhaka Hospital of icddr,b (International Centre for Diarrhoeal Disease Research, Bangladesh) from April 2010 to April 2014 who had their reports of arterial blood gas analyses were enrolled in the study. We compared clinical and laboratory characteristics between the study children with (cases = 74) and without metabolic acidosis (controls = 65). Metabolic acidosis was defined if pH < 7.35 and HCO 3 < 22 mmol/L in ABG. Cases had higher mortality (53% vs 29%, P = .01) compared to controls. After adjustment of potential confounders, for instance, hypokalemia and dehydration, the cases were independently associated with severe sepsis and raised serum creatinine (for both P < .05). Thus, early identification of these features of metabolic acidosis in diarrheal children may help clinicians to have prompt management that may further help reduce mortality in such children especially in resource-limited settings.